Assessment of Pupils’ Knowledge and Practices Towards Prevention and Control of Tungiasis Infestation in Ugenya Sub County, Kenya - J, Mwai; E, Githinji; A, Odiwuor; C, Oduor; G, Kotonya; S, Njenga; C, Mwandawiro (Journal of Tropical Diseases and Medicine, 2018)
Background: Tungiasis is a parasitic tropical disease caused by female Tungapenetranswhich has remained an important public health problem and it affects resource-poor communities causing different health disabilities hence the need for behavior change. Main objective of the study was to determine factors influencing prevention and control of tungiasis infestation among school age children in Ugenya Sub County, Kenya. Methods: A descriptive cross sectional design and utilizing quantitative data collection method. Simple random sampling technique was applied to select the participants. Quantitative data was collected through a pretested structured questionnaire. The data was keyed-into excel and analyzed using SPSS version 23. Results: Study findings indicate that majority of the pupils infested with tungiasis were in classes 5 – 6 at 191(49%). Male participants were 200 (51%), while 185(49%) were female. Gender of pupils (χ2=4.383a, df=1, P<0.005) and household head occupation (χ2=44.729, df = 28, P<0.005) had a statistical significance with tungiasis infestation. Further significance was noted between participants who had ever heard of jiggers (χ2=6.361, df=1, P<0.005), Knowledge on important causes of jiggers (χ2=36.482, df = 9, P<0.005), mode of disease transmission (χ2=17.215, df = 5, P<0.005), signs and symptoms (χ2=4.088, df = 1, P<0.005), seriousness of jiggers in the area (χ2=13.175, df = 1, P<0.005) as well as pupil’s wearing of shoes (χ2=3.934, df = 1, P<0.005) and tungiasis infestation. Conclusions: Study concludes that tungiasis is still a big problem in rural settings and knowledge on tungiasis infestation does not translate to prevention and control in the areas. More emphasis should be given to improving practices touching on personal hygiene and health education to increase awareness both at school and in the households.
Keywords: Knowledge; Attitude; Practices; Tungiasis; Prevention; Infestation; Control; Ugenya.